Due vie all'abbondanza? «Le regole seguite dalla Natura sono adeguate ad essa. Quelle seguite dall’uomo sono adeguate per l’uomo» - Roberto Finzi (Montesquieu.it, 2015)
Produce more or want less? The question, posed by anthropology, is here presented starting from the ancient myth of the golden age and its end determined by Jupiter curis acuens mortalia corda. At this point in history born the property – «the only case where the origin of natural rights is not altogether plain» (A. Smith) – leading men to «la possession des choses – says the Encyclopédie – dont ils ont un besoin naturel; mais elle leur donne en même tems la notion d’une infinité de besoins chimériques qui les pressent mille fois plus vivement que des besoins réels». The way is therefore to produce more and more for growing needs. The knowledge of the «savages» of America strengthens this tendency, whose main «instrument» is the division of labor. Gradually, however, there is a clash or a contradiction between «the rules» which nature «follows [...] fit for her» and those which man «follows for him»